2004
DOI: 10.1080/jmf.16.2.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal infections during pregnancy: epidemiological and microbiological aspects

Abstract: Cervicovaginal infections were significantly associated with PROM (p<0.0001), pPROM (p<0.0001) and preterm delivery (p<0.0001), but not with intrauterine death. The association with mid-trimester miscarriage approached statistical significance (p=0.06). The main risk factors for cervicovaginal infections were country of origin, age under 25 years, age at first intercourse under 15 years, more than ten partners, more than one partner in the past 6 months, prior abortions, past STDs and HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In pregnancy, Hillier et al (14) found BV‐positive women more likely to be single, young, of Hispanic race, to have had early first sexual intercourse, to be less educated, and to have lower income than BV‐negative women. Benedetto et al (15) found that ethnicity, age under 25 years, age at first intercourse under 15 years, more than ten partners, more than one partner in the past 6 months, prior abortions, past sexually transmitted diseases, and HIV infection were the main risk factors for cervicovaginal infections in pregnancy including BV.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, Hillier et al (14) found BV‐positive women more likely to be single, young, of Hispanic race, to have had early first sexual intercourse, to be less educated, and to have lower income than BV‐negative women. Benedetto et al (15) found that ethnicity, age under 25 years, age at first intercourse under 15 years, more than ten partners, more than one partner in the past 6 months, prior abortions, past sexually transmitted diseases, and HIV infection were the main risk factors for cervicovaginal infections in pregnancy including BV.…”
Section: Introductionmentioning
confidence: 99%
“…These are often negatively selected by nature and mostly end up in a miscarriage [19,20]. Several infections have been also identified as potential cause of early miscarriage [21] with specifically, 15% of early miscarriages and 66% of late miscarriages been associated with infections [22].…”
Section: The Known Causes Of Rmmentioning
confidence: 99%
“…Even other studies (16) have revealed its significance in predicting PROM, PPROM and preterm delivery. In fact when compared to a wet mount and cytology methods, it ranks at the top as stated in the International Journal of Tropical Medicine .…”
Section: Methodsmentioning
confidence: 99%